Political systems in the era of Al-Mustansir Billah Al-Fatimid: (427-487 AH / 1035-1094 AD) - Hindi, Hazem (Al-Adab Journal, 2024)
The Fatimid states were distinguished from their predecessors by being a state based on a philosophy and a religious movement represented by the Fatimid call based on encouraging the movement of thought, culture and science. The Fatimid state ruled fourteen caliphs and the caliph al-Mustansir Billah (427-487 AH / 1035-1094 AD) was the eighth in the succession of their successors, who is considered the longest reigning Fatimid caliph, with a succession of sixty years and four months. The Fatimid Caliphate suffered in his succession from political, economic and social conditions that led to confusion of the internal situation in Egypt in that era, especially as he assumed power as a child unable to manage the affairs of the caliphate, so the reins of government devolved to his mother being his guardian and has remained a guardian until he reached the age of majority, as well as the Caliph Al-Mustansir fell under the influence of bad men, and perhaps the biggest manifestation of that situation is the speed of changing ministers in his reign, as they became falling Very quickly, as the ministry in his succession shifted from the ministry of the owners of pens to the ministry of the owners of swords who controlled the reins of power, and the caliphs later became a puppet in their hands moving them as they pleased . In his caliphate, Egypt was also swept by an economic crisis that lasted for more than seven years, during which Egypt witnessed a great famine known in history books as the Mustansiriya severity. Our choice came to study the topic tagged (political systems in the era of Al-Mustansir Billah Fatimid. The research has proven that the period of the caliphate of al-Mustansir Billah (427-487 AH / 1035-1094 AD) was exemplary in time. It was found through this research that the personality of the Caliph Al-Mustansir Billah was a weak-hearted personality did not play in life his role, but left it to others. The favor of the ministers owners of swords and the few owners of the pen, and explain the large number of those who took over the ministers sometimes for one day or for several days to the weakness of the caliph, as the research proved the control of ministers with swords on the reins of government and the conduct of the state and governance as they want and wish. The research proved that the economic crisis that Egypt was exposed to in his caliphate, called the Mustansiriya severity, was very severe, as it led the Fatimid caliphate to lose its content, identity and youth and to live in long old age and was one of the reasons for the collapse of the Fatimid state and its fall in (567 AH / 1171 AD).